Relationship between symptoms of allergic rhinitis and their severity with specific allergens and duration of allergic rhinitis - Ceyda Akın Öçalan, Fatma; Özcan, Müge; Öçalan, Ramazan; Fuat Yılmaz, Yavuz; Ünal, Adnan (ENT Updates, 2013)
Objective: To determine whether specific allergens induce specific symptoms or not, and whether symptoms and the severity of the symptoms change in the parallel with the increase in the duration of allergic rhinitis or not. Methods: This trial was conducted through retrospective screening of the data forms of patients who had presented to our ENT-Allergy Unit with allergic symptoms, and diagnosed as allergic rhinitis based on the history, examination and prick test or serum specific IgE results. Results: A total of 235 patients were enrolled in the trial. Nasal discharge and postnasal drip were significantly less common in tree allergies, itching and watering of the eyes were more common in grass allergies. Redness in the eyes was significantly less common in weed allergies. Nasal discharge was significantly less common in allergy against animal epithelium and hair. Sneezing and itching/watering of the eyes were significantly less, while hyposmia was more frequently seen in house dust-mite allergies. Comparison of the duration of allergic rhinitis with the frequency of symptoms revealed a statistically significant increase in hyposmia and redness in the eyes in seasonal allergic rhinitis, parallel to the increase in the duration of allergic rhinitis. Conclusion: We suggest that specific symptomatic treatments directed against the allergen(s) which also shorten duration of allergic rhinitis may be an option in the management of allergic rhinitis and will yield positive outcomes in terms of improved control of the symptoms and hence quality of life of the patients.